Electrocatalytic oxygen reduction and hydrogen evolution reactions on phthalocyanine modified electrodes: Electrochemical, in situ spectroelectrochemical, and in situ electrocolorimetric monitoring - KOCA, ATIF (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
This study describes electrochemical, in situ spectroelectrochemical, and in situ electrocolorimetric monitoring of the electrocatalytic reduction of molecular oxygen and hydronium ion on the phthalocyanine-modified electrodes. For this purpose, electrochemical and in situ spectroelectrochemical characterizations of the metallophthalocyanines (MPc) bearing tetrakis-[4-((4'-trifluoromethyl)phenoxy)phenoxy] groups were performed. While CoPc gives both metal-based and ring-based redox processes, H2Pc, ZnPc and CuPc show only ring-based electron transfer processes. In situ electrocolorimetric method was applied to investigate the color of the electrogenerated anionic and cationic forms of the complexes. The presence of O-2 in the electrolyte system influences both oxygen reduction reaction and the electrochemical and spectral behaviors of the complexes, which indicate electrocatalytic activity of the complexes for the oxygen reduction reaction. Perchloric acid titrations monitored by voltammetry represent possible electrocatalytic activities of the complexes for hydrogen evolution reaction. CoPc and CuPc coated on a glassy carbon electrode decrease the overpotential of the working electrode for H+ reduction. The nature of the metal center changes the electrocatalytic activities for hydrogen evolution reaction in aqueous solution. Although CuPc has an inactive metal center, its electrocatalytic activity is recorded more than CoPc for H+ reduction in aqueous solution. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Phthalocyanine; Spectroelectrochemistry; Electrocatalyst; Hydrogen evolution reaction; Oxygen reduction reaction; METAL-FREE; COBALT PHTHALOCYANINE; PROTON REDUCTION; CARBON-DIOXIDE; METALLOPHTHALOCYANINES; SUBSTITUENTS; ELECTROREDUCTION; COMPLEXES; CATALYSTS; CO(II)